Cost of speech-language interventions for children and youth with foetal alcohol spectrum disorder in Canada. (December 2014) - Popova, Svetlana; Lange, Shannon; Burd, Larry; Shield, Kevin; Rehm, Jürgen
Abstract This study, which is part of a large economic project on the overall burden and cost associated with Foetal Alcohol Spectrum Disorder (FASD) in Canada, estimated the cost of 1:1 speech-language interventions among children and youth with FASD for Canada in 2011. The number of children and youth with FASD and speech-language disorder(s) (SLD), the distribution of the level of severity, and the number of hours needed to treat were estimated using data from the available literature. 1:1 speech-language interventions were computed using the average cost per hour for speech-language pathologists. It was estimated that ˜ 37, 928 children and youth with FASD had SLD in Canada in 2011. Using the most conservative approach, the annual cost of 1:1 speech-language interventions among children and youth with FASD is substantial, ranging from $72.5 million to $144.1 million Canadian dollars. Speech-language pathologists should be aware of the disproportionate number of children and youth with FASD who have SLD and the need for early identification to improve access to early intervention. Early identification and access to high quality services may have a role in decreasing the risk of developing the secondary disabilities and in reducing the economic burden of FASD on society.